1994
DOI: 10.1002/mc.2940090202
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive ap‐1 dna binding and transactivating ability of malignant but not benign mouse epidermal cells

Abstract: The mouse epidermal cell line 308 contains an activated Ha-ras gene and forms benign papillomas when transplanted to the skin of athymic nude mice. A radiation-associated malignant variant of this cell line, 308-10Gy5, has been isolated and shown to form squamous cell carcinomas in nude mice. To further examine the molecular events involved in malignant conversion of 308-10Gy5, we assessed the activator protein-1 (AP-1) binding and transactivating ability of 308 and 308-10Gy5. In nuclear protein extracts of 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 18 publications
1
52
0
Order By: Relevance
“…Transformation of ®broblasts by oncogenes, such as raf and ras, have also been shown to be dependent on AP-1 activity (Johnson et al, 1996;Lloyd et al, 1991;Rapp et al, 1994;Suzuki et al, 1994). The role of AP-1 in transformation is not limited to ®broblasts, since mouse and human squamous cell carcinomas expressing the dominant negative Jun mutant have reduced tumourigenicity and in vitro invasiveness (Domann et al, 1994;Dong et al, 1997;Malliri et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Transformation of ®broblasts by oncogenes, such as raf and ras, have also been shown to be dependent on AP-1 activity (Johnson et al, 1996;Lloyd et al, 1991;Rapp et al, 1994;Suzuki et al, 1994). The role of AP-1 in transformation is not limited to ®broblasts, since mouse and human squamous cell carcinomas expressing the dominant negative Jun mutant have reduced tumourigenicity and in vitro invasiveness (Domann et al, 1994;Dong et al, 1997;Malliri et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies have shown that blocking AP-1 transactivation in malignant cell lines could inhibit their ability to form tumors upon subcutaneous injection into athymic nude mice (Domann et al, 1994). Furthermore, inactivation of AP-1 by aspirin and salicylates or retinoic acid correlated with inhibition of tumor promoter induced transformation and tumorgenesis Huang et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…From studies utilizing reporter constructs measuring AP-1-dependent gene expression, the induction of AP-1 transactivation also has been shown to be essential for tumor promotion and progression in cell culture models (Dong et al, 1994(Dong et al, , 1997Li et al, 1998;Domann et al, 1994). In JB6 and human keratinocyte models, expression of dominant negative c-jun can block induced AP-1 activity and neoplastic transformation (Dong et al, 1994(Dong et al, , 1997Li et al, 1998;Domann et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In JB6 and human keratinocyte models, expression of dominant negative c-jun can block induced AP-1 activity and neoplastic transformation (Dong et al, 1994(Dong et al, , 1997Li et al, 1998;Domann et al, 1994). TPA-induced upregulation of the AP-1 transcription factor complex occurs prior to TPAinduced ODC gene expression.…”
Section: Introductionmentioning
confidence: 99%